Mediating Criminal Conversion in City Comedy and Domestic Tragedy - Coursey, Sheila (Early Theatre, 2025)
This article explores the stakes of discerning criminal conversion on the early modern stage, particularly when city comedies and domestic tragedies mediate contemporaneous London events. These plots offered an intersection between contemporaneous pamphlets that framed criminality as a distinct social identity and early English dramatic practices representing spiritual conversion. The Roaring Girl defended Moll Cutpurse’s criminal adjacency by framing her urban mediation as a hagiography akin to the Digby Play of Mary Magdalene. In contrast, domestic tragedies used hybrid personification to offer ambiguity about the spiritual or forensic state of mediators or go-betweens in criminal conspiracies. These paradigms offer diverging responses to antitheatrical warnings about the associative risks of playgoing.